Maternal Mortality : Report June, 1932 (London : The Maternal Mortality Committee)
1932-06 1932 1930s 20 pages circumstances were such that confinement at home was highly undesirable was within reasonable reach of and could enter a Maternity Home." The Westminster City Council report a scheme which is worked from the Westminster Hospital, and which is admirably organised. They have a district midwife working from the hospital. Accommodation at so much per head in hospital is arranged for all classes of maternity cases. All the ancillary services are in force. The whole scheme is worked in conjunction with the Hospital, the authorities there being anxious to co-operate. Newport (Mon.) gives evidence of deplorable overcrowding, and urges that adequate Maternity Hospital beds would provide the solution. It has been suggested that the general practitioners taking part in ante-natal work under a Local Authority are often insufficiently equipped with knowledge. On the other hand, although there may be ground for complaint in some quarters we feel that the work is educative to the practitioner and helpful to the patient and her midwife, and that it would not be wise to discourage the calling in of general practitioners. On the whole it is likely that only the best and keenest will take up this work, and it must be remembered that when a scheme for ante-natal supervision by general practitioners is arranged the condition that reports shall be made to the Medical Officer of Health is an additional safeguard. We note in these Reports, notably in a large centre of population (Wolverhampton) how prejudice against maternity wards in Institutions has disappeared, and from comparison of the Reports we have come to the conclusion that the popularity of these Hospitals depends on their being thoroughly brought up-to-date. This need seems to us to be one of the most urgent and the present moment is the obvious opportunity for removing, by complete reconditioning and adequate equipment, the stigma from Public Assistance Hospitals which are now being "taken over." Midwives. The recommendations of the Departmental Committee on the Training and Employment of Midwives seems to be already bearing fruit ; some of the districts, such as Durham, have been for some time trying to pull up the standard of their nursing and eliminate the handy women. But as far as we can ascertain, the pay received by the midwife is still inadequate. The Medical Officer for Glamorgan speaks of the unattractiveness of the work in respect of pay, status, and of its unavoidably tedious conditions, "a modest living gained with much anxiety and loss of sleep." Here 86 per cent. of the local midwives are trained women. The Medical Officer of Health for Bolton, in urging better conditions, says that the midwives "give a better service than (17) 292/824/1/58